Correction to: Numerical simulation of RC frames infilled with RC walls for seismic strengthening of existing structures - Georgiou, Elpida; Kyriakides, Nicholas; Chrysostomou, Christis (My University, 2022)
This correction is published as vendor overlooked several proof corrections. Original article has been corrected.
Keywords: RC frames; RC walls; Seismic strengthening; Existing structures